Changes in body mass index, height, and weight in children during and after therapy for acute lymphoblastic leukemia. Issue 21 (25th October 2018) - Browne, Emily K.; Zhou, Yinmei; Chemaitilly, Wassim; Panetta, John C.; Ness, Kirsten K.; Kaste, Sue C.; Cheng, Cheng; Relling, Mary V.; Pui, Ching‐Hon; Inaba, Hiroto
Abstract: Background: Children with acute lymphoblastic leukemia (ALL) have an increased risk of obesity and short stature. To the authors' knowledge, data regarding patients treated on contemporary protocols without cranial irradiation are limited. Methods: Changes in z scores for body mass index (BMI), height, and weight from the time of diagnosis to 5 years off therapy were evaluated using multivariable analysis in 372 children with ALL who were aged 2 to 18 years at the time of diagnosis and were enrolled on the St. Jude Children's Research Hospital Total XV protocol from 2000 through 2007. Results: The percentage of overweight/obese patients increased from 25.5% at the time of diagnosis to approximately 50% during the off‐therapy period. Median BMI z scores increased significantly during glucocorticoid therapy (induction: ∆0.56; 95% confidence interval [95% CI], 0.29‐0.64 [ P <.001]; and reinduction II: ∆0.22; 95% CI, 0.13‐0.49 [ P =.001]) and during the first year after therapy (∆0.18; 95% CI, 0.08‐0.46 [ P =.006]). Among patients who were of healthy weight/underweight at the time of diagnosis, those aged 2 to <10 years at diagnosis had a significantly higher risk of becoming overweight/obese during or after therapy compared with those aged ≥10 years ( P =.001). Height z scores declined during treatment and improved after therapy. Being aged 2 to <10 years at the time of diagnosis, being of low‐risk status, having a white blood cell count < 50×10 9 /L at the time of diagnosis, and having negative central nervous system disease were associated with significantly better improvements in z scores for height during the off‐therapy period compared with being aged ≥10 years, being of standard‐risk/high‐risk status, having a white blood cell count ≥ 50×10 9 /L, and having positive central nervous system disease, respectively. Conclusions: The results of the current study demonstrate that obesity is prevalent, and height growth, especially in patients with identified risk factors, appears compromised. Multidisciplinary intervention should begin during induction therapy and continue during the off‐therapy period. Abstract : The results of the current study demonstrate that body mass index z scores increase during induction therapy and remain elevated even after the completion of therapy. Therefore, multidisciplinary intervention for obesity should begin during induction therapy and continue during the off‐therapy period. Although z scores for height appear to decline during therapy and improve after therapy completion, they remain low in patients aged ≥10 years at the time of diagnosis, in those with standard‐risk/high‐risk status, in those with a white blood cell count of ≥50×10 9 /L at the time of diagnosis, and in those with positive central nervous system disease.